Ethical leadership, ethical organizational culture, and their impact on organizational effectiveness in online platform businesses - Lertsukkheerat, Tanapat; Kongyoungyune, Rungraditt (Journal of Dhamma for Life, 2025)
This study explores the relationship between ethical leadership, ethical organizational culture, and organizational effectiveness in online platform-based private organizations. The research aimed to 1) examine ethical leadership, ethical organizational culture, and organizational effectiveness; 2) investigate the correlations between ethical leadership, ethical organizational culture, and organizational effectiveness; and 3) analyze the impact of ethical leadership and ethical organizational culture on organizational effectiveness. A quantitative research methodology was employed, utilizing a structured questionnaire with a 5-point Likert scale. The target population comprised 758 private organizations using online platforms, with a sample of 294 organizations. Statistical analyses included percentage, mean, standard deviation, Pearson correlation coefficient, and multiple regression analysis. Key findings revealed 1) high levels of ethical leadership, ethical organizational culture, and organizational effectiveness across all dimensions; 2) a strong positive correlation between ethical leadership and ethical organizational culture (r = 0.68, p < 0.01), and a significant positive relationship between ethical leadership and organizational effectiveness (r = 0.718, p < 0.01); and 3) critical components of ethical leadership and ethical organizational culture significantly influenced organizational effectiveness, explaining 71.30% of the variance (Adjusted R² = 0.713) at a statistically significant level (p < 0.05).